Triple-layered security system: reliable and secured image communications over 5G and beyond networks - Tarek Srour; Mohsen A. M. El-Bendary; Mostafa Eltokhy; Atef E. Abouelazm (Scientific Reports)
Abstract The vision of 5G and beyond networks is geared towards linking undersea, terrestrial, and space networks together. This vision involves transferring a massive amount of data with very high levels of security. This paper presents the proposed vision of 5G and beyond security to build a research gap of existing and related technique that lack the adaptation, boosting gradient and complexity analysis, through design and evaluate the adapted and graded security system. This paper focuses on designing a security approach to make up the lacks of existing techniques. The paper proposes a Loss-less Triple-level security system that secures the data without loss and high quality of extracted messages. The Triple-level security system consists of three combined/ merged security levels, the classified images are encrypted by two chaos-based tools, the encrypted images are embedded into another fake image or audio file using Singular Value Decomposition-Discrete Wavelet Transform (SVD-DWT) based techniques. Various simulation experiments have been executed to find the best integration between two-Dimensional (2D) Logistic map, SVD, and baker map techniques to ensure the integrity of plaintext and the transparency of the proposed approach. The result analysis of the various computerized experiments reveals that the time of algorithms are 2.13s for ciphering/hiding and 1.57s for deciphering/extracting. Hence, the time complexity of the proposed approach superiors the existing and related research works. The simulation results indicates a 100% perfect match between the original and decrypted. The performance evaluating of the proposed technique proves its robustness, low complexity and high reliability, where the original and extracted message similarity is 100%. The advanced wireless networks require reliable graded complexity security tools with various levels capabilities, therefore, the proposed adapted complexity/levels security system is suitable and applicable for 5G/beyond networks.